2002
DOI: 10.1177/0146167202287011
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Assimilation and Differentiation Needs on Perceived Group Importance and Judgments of Ingroup Size

Abstract: At the heart of optimal distinctiveness theory is the idea that a group’s level of inclusiveness is a significant determinant of how well that group can meet members’ needs for assimilation and differentiation. In two studies, this principle was demonstrated by experimentally manipulating both needs and examining their effects on perceptions of ingroup size and on the perceived importance of ingroups that vary in level of inclusiveness. It was predicted that assimilation need would lead to a preference for inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
137
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(148 citation statements)
references
References 18 publications
7
137
1
1
Order By: Relevance
“…According to optimal distinctive theory (Brewer, 1991;Pickett et al, 2002), individuals are hypothesized to have the following two choices in order to satisfy needs for assimilation. First, they will shift their belief to be admitted into the majority within the in-group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to optimal distinctive theory (Brewer, 1991;Pickett et al, 2002), individuals are hypothesized to have the following two choices in order to satisfy needs for assimilation. First, they will shift their belief to be admitted into the majority within the in-group.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal distinctive theory (Brewer, 1991;Pickett, Silver, & Brewer, 2002) asserts that ingroup biases or identities are decided by two motivations: assimilation and differentiation. Individuals have to satisfy their need for assimilation when they associate with a minority in a categorical in-group.…”
mentioning
confidence: 99%
“…personal identity motive) but also varies in response to changes in the features of the group (i.e. social identity motive) (see also Baumeister & Leary, 1995;Pickett, Silver & Brewer, 2002;Vignoles, Chryssochoou, & Breakwell, 2000). Spears et al (2009) used an experimental design that manipulated the meaningfulness of minimal groups, demonstrating that group meaning (i.e.…”
Section: Social Identity Motives (Group Content Individual Processes)mentioning
confidence: 99%
“…In several studies, Brewer and colleagues have tested and found an interaction of the distinctiveness motive with one indicator of distinctiveness, group size (e.g., Brewer et al, 1993;Pickett, Silver, & Brewer, 2002). For example, Pickett et al instructed participants to think of a situation where they felt similar to others.…”
Section: Distinctiveness (Autonomy and Difference)mentioning
confidence: 99%
“…Although this distinction has not been explicitly made in social identity research before, it is evident in the operationalization of the belonging motive in some studies (e.g., see Pickett et al, 2002, as discussed above) and parallels Mael and Ashforth's (2001) distinction between the social identity functions of depersonalized belonging (''the sense of community based on the perception of common identity'') and personalized belonging (''attachment based on interpersonal attraction'', p. 201).…”
Section: Belongingness (Affiliation and Assimilation)mentioning
confidence: 99%